Studi Co-Precipitation Tembaga (II) Menggunakan Coprecipitant Al(OH)3 pada Sungai Batang Arau Kota Padang Diukur dengan Metoda Spektrofotometri Serapan Atom (SSA) - Yusuf .; Indang Dewata; Edi Nasra (Jurnal Periodic Jurusan Kimia UNP, 2013)
A study in the development co-precipitation method and natural samples was applied to the Batang Arau River in Padang City. Sampling was done once in the month of November 2012, by random sampling on the selected point along the river which was considered to represent the river. Sampling points taken in the river upstream Lubuk Paraku Kor were named sample 1, the sampling points in the middle of the river called hilalang padang besi were called as sample 2, the third sampling points downstream to the mouth of the river were called the sample stream 3. The analysis was performed with the optimization of pH and volume optimization before it was applied to the sample. The result was the determination of the optimum pH conditions co-precipitant Al(OH)3 with atomic absorption spectroscopy air acetylene flame occurred at pH 6, the optimum volume coprecipitant used in the co-precipitation method was the addition of Al(OH)3 as much as 11 mL. Content of Copper (II) obtained at the optimum conditions at upstream was 2,22ppm, in the middle of the river was 1,294 ppm and 1,2 ppm was the content at the river mouth, with an average concentration factor of 104 times compared to direct measurement without the co-precipitation. Quality Standards based on PP. 82 Year 2001 Class II was still in the limited threshold 0,02 ppm.